Therapeutic potential of α-glucosidase inhibitors in type 2 diabetes mellitus: an evidence-based review - Joshi, Shashank R; Standl, Eberhard; Tong, Nanwei; Shah, Parag; Kalra, Sanjay; Rathod, Rahul (Expert opinion on pharmacotherapy, 2015)
Postprandial hyperglycemia (PPHG) contributes to micro- and macro-vascular complications more than fasting hyperglycemia in patients with type 2 diabetes mellitus. Due to the traditional carbohydrate-rich diet, Asians, particularly Indians and Chinese need agents to control the higher risk of uncontrolled PPHG. Targeting PPHG with α-glucosidase inhibitors (AGIs), either alone or in combination with other oral hypoglycemic agents and insulin, provide overall glycemic control with transient mild gastrointestinal disorders. Treatment with AGIs, especially acarbose, has also shown to provide beneficial effects on lipid levels, blood pressure, coagulation factors, carotid intima-media thickness and endothelial dysfunction. New insights of acarbose therapy obtained like increased activity of gut hormones and improved gut microbiota may explain the benefits on weight, whereas increased production of H2 may explains its cardiovascular benefits to some extent. A systematic search strategy was developed to identify randomized controlled trials in MEDLINE, PubMed, EMBASE and ongoing trials databases. AGIs as a class and acarbose in particular, are most useful in combatting PPHG and glucose variability across the spectrum of diabetes therapy, particularly in Asian patients. Together with their effects on incretin hormones and gut-microbiota AGIs can be considered beyond glycemic control as 'cardio-protective agents.'